Prediksi Curah Hujan di Kabupaten Magelang Menggunakan Metode Fuzzy Time Series Untuk Mendukung Pengambilan Keputusan - Ginanjar Prianggoro Kasih; Uky Yudatama; R Arri Widyanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Rainfall prediction is an important aspect in water resource management, agriculture and disaster mitigation. Magelang Regency, as one of the regions in Indonesia that has high rainfall variability, requires accurate prediction methods to support planning and decision making. This research aims to apply the Fuzzy Time Series method which is known to be effective in handling uncertain and fluctuating time series data in predicting rainfall in Magelang Regency. Monthly rainfall data for 2022–2024 used in this research was obtained from the Public Works and Spatial Planning Department. The research results show that the Fuzzy Time Series method is able to provide rainfall predictions with a good level of accuracy. This is indicated by the Mean Absolute Percentage Error (MAPE) value of 16.19%, which is in the good category according to prediction standards. This success shows that the Fuzzy Time Series method can be an effective alternative in predicting rainfall, especially in areas that have complex rainfall patterns such as Magelang Regency.